Air Rage Arrangement Between the United Kingdom and Indonesia Based on the Tokyo Convention 1963 - Naek Siregar (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
The implementation of international and national civil aviation must refer to applicable international and national legal norms to ensure the safety of passengers, flight crew, aircraft, and goods transported. To meet safety and security standards, each country must regulate flight security programs that refer to the regulations of the International Civil Aviation Organization (ICAO). Indonesia and the UK must meet these standards in dealing with perpetrators of air rage. Indonesia and the United Kingdom are the countries that participated in the ratification of the Convention on Offices and Certain Other Acts Committed on Board Aircraft, commonly called The Tokyo Convention 1963. Both countries have a legal obligation to implement the convention in their national law. A distinctive feature between Indonesia and the United Kingdom makes the implementation of the Tokyo Convention 1963 in that country different but still has the same goal of ensuring flight safety and security.